(3GdOQQ GdeOQhRI aj TQM GdCQLhRIs - (3efUhQ GdTGaYj GdeMdis; (3eMH GdOjf CHh GdhdjO eMeO Hf eMeO Hf GdTMfI,J (B815 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje jbhd efUhQ GdTGaYi GdeMdi hHYO abO SCdfi Cf CcJH TQMkG UZjQ GdMLe Sgd GdeCNP Ydi efXheI GdTjN GdaGVd eMeO Hf GdhdjO eMH GdOjf Hf GdTMfI hgj GdJi ai Yde GdeYGfi hGdHjGf s
(3BNQgG (B:s
(3hbhd GdfGXe GfJgi GdebGd jYfi Ydi eG bGdg hdjS eQGOg EfJgGA GdebGd GdPi gh HeYfi GdNJGe hgPG BNQ eG jSQg Gddg JYGdi Ydi gPg GdCQLhRI hjNJe dfG HGdEjeGf hgh QGmV YfG HLGg eMeO Udi Gddg Ydjg hSde s
(3GdfSNI HgG MhGTs
(3HChdgG hbajI HGSe YdGeI HjQhJ GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbi eDQN SfI (B1373(3g`s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdHdGZIs